Biodiesel Production from Insects: From Organic Waste to Renewable Energy - Nguyen, Hoang C.; Nguyen, Ngoc Tuan; Su, Chia-Hung; Wang, Fu-Ming; Tran, Tuyet Nhung; Liao, Ying-Tzu; Liang, Shih-Hsiang (Current Organic Chemistry, 2019)
The conversion of organic wastes into biodiesel has become an attractive solution to address waste surplus problems and energy depletion. Oleaginous insects can degrade various organic wastes to accumulate fat-based biomass, thus serving as a potential feedstock for biodiesel production. Therefore, the use of insects fed on organic waste for biodiesel production has increasingly attracted considerable investigations. In recent years, different insect species have been studied for their efficiency in converting various organic wastes and for producing biodiesel from their fat. Several methods have been developed for biodiesel production from insects to improve yields and reduce production costs and environmental impacts. This review summarizes the latest findings of the use of insects for converting organic wastes into biodiesel. The production processes and fuel properties of biodiesel produced from insects are also discussed.
Keywords: Bioconversion